Energy Efficiency as a Driver of More and Better Goods and Services - Benoit, Philippe; Zinetti, Silvia; De Wit, Joerie; Lukas, Aditya (World Bank, Washington, DC, 2021)
Energy efficiency is seen more often as a means of reducing energy consumption and costs than as a way to expand the production of goods and services. But it can help raise a company’s manufacturing capacity, improve the quantity and quality of a city’s water supply, and provide more heating and cooling to improve attendance and learning in schools - all while keeping energy costs down. It is important to recognize such benefits of energy efficiency for low- and middle-income countries - and to factor them into economic assessments of projects and programs.